THE POLITICAL CONSIOUSNESS IN AFRICAN LITERATURE: A READING OF SELECTED PLAYS OF FEMI OSOFISAN - Sola Owonibi (European Scientific Journal, ESJ, 2014)
The major pivot around which the art of literary creativity revolves is life. A work of art can neither exist in a vacuum nor can it be divorced from the myriad of socio-political factors or social realities that negatively or positively influence the worldview of man. These factors can either be political, historical, biographical, or sociological. What this entails is that literature derives its main essence from life, as the creative writer is provoked to present the losses and gains, the ills and virtues, of a society with a view to highlighting or sensitizing the people to the solutions of these problems. A work of art also entertains as it educates. This confers on literature the ability to influence human beings psychologically, spiritually, and physically depending on the sensitivity and/or the world-view of the writer. This paper explores how Femi Osofisan sees politics as a tool of social organization in his dramaturgy with a critical study of six of his plays: A restless Run of Locusts (1975), The Chattering and the Song (1977), Who is Afraid of Solarin (1978), Once Upon Four Robbers (1982), Morountodun and Other Plays (1982) and Mid-Night Hotel (1986).